Analysis of Digital Payment Usage by Field of Work - Naufal Dicka Loviananda; Ratna Fitri Astuti; Noor Ellyawati; Vitria Puri Astuti (SOSIOEDUKASI, 2025)
The use of digital money in various circles has differences both in frequency and reasons for use. The study aims to determine the use of digital payments based on the field of work and the field of work that utilizes digital payments the most in Samarinda City. The research used a survey type of research, with a descriptive quantitative approach. The sample size was 96 respondents who were residents of Samarinda City with groupings based on field of work. Data collection was done through distributing questionnaires. The research used descriptive analysis and calculation of data percentages, which were processed through the Microsoft Excel application. The results showed that the use of digital payments in Samarinda City provides convenience for people from various occupational groups. People already feel the security, speed, convenience, and efficiency of transactions in using digital payments. 60% of people in Samarinda City based on the field of work in a week use digital payments several times to fulfill their needs.